1997
DOI: 10.1016/s1010-7940(97)00084-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of imaging TNM [(i)TNM] and pathological TNM [pTNM] in staging of bronchogenic carcinoma

Abstract: Even with present-day CT scanners (i)TNM provides no accurate staging and routine mediastinoscopy is necessary for precise mediastinal lymph node staging. Likewise, (i)T3 and (i)T4 determinations are unreliable and should not contraindicate thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 16 publications
2
45
0
4
Order By: Relevance
“…Nonetheless, multislice CT scan showed a 60.0% positive predictive value in assessing tumor spread to proximal vessels. This result is similar to that reported in previous studies employing conventional CT [7][8][9][10][11], while it is somewhat worst than that reported in one study by thin-section electron-beam CT [26] in which accuracy, sensitivity, and specificity in evaluating invasion of the pulmonary artery were 75%, 77.8%, and 71.4%, respectively. It is worth noting that, in this study, if one considers left-sided FVP only, negative predictive value was 100%, which suggests a high accuracy in detecting resectable lesions in these patients.…”
Section: Commentsupporting
confidence: 90%
“…Nonetheless, multislice CT scan showed a 60.0% positive predictive value in assessing tumor spread to proximal vessels. This result is similar to that reported in previous studies employing conventional CT [7][8][9][10][11], while it is somewhat worst than that reported in one study by thin-section electron-beam CT [26] in which accuracy, sensitivity, and specificity in evaluating invasion of the pulmonary artery were 75%, 77.8%, and 71.4%, respectively. It is worth noting that, in this study, if one considers left-sided FVP only, negative predictive value was 100%, which suggests a high accuracy in detecting resectable lesions in these patients.…”
Section: Commentsupporting
confidence: 90%
“…No distant metastases M1 Distant metastases present one-half of the TNM stages derived from CT agree with operative staging, with patients being both under and over staged [91,92]. However, quick access to investigation, high histological confirmation rates (at bronchoscopic/transthoracic biopsy or at thoracotomy), routine CT scanning and review of every patient by a thoracic surgeon is known to substantially increase successful surgical resection [93].…”
Section: M0mentioning
confidence: 89%
“…MCLOUD et al [103] also found that 37% of nodes, which were 2-3 cm in diameter, did not contain metastases at thoracotomy. More recently in a study of hila and mediastinal nodes at CT compared to pathological examination, sensitivities and specificities for metastatic involvement were only 48% and 53% with an overall accuracy of 51% [92]. Despite these statistics, CT is still recommended as the standard strategy for the investigation of lung cancer by the Canadian Lung Oncology Group [109] after the study of 685 patients, CT and mediastinoscopy in all patients proving too expensive.…”
Section: Nodal Statusmentioning
confidence: 99%
“…Cangemi et al (2) report an accuracy of 91% and 27% for the staging of T 3 and T 4 lung cancers, respectively, with the use of chest computerized tomography (CT). Gdeedo et al (3) report that overall, CT staging for T 3 or T 4 lung cancers was correct only 50% of the time. Comparisons of clinical and pathologic staging generally show that clinical staging underestimates the true pathologic stage.…”
Section: Stagingt 3 and T 4 Lung Cancermentioning
confidence: 99%